The Discursive Construction of Risk and Trust in Patient Information Leaﬂets - Fage-Butler, Antoinette Mary (HERMES - Journal of Language and Communication in Business, 2011)
There is wide recognition that the communication of risk in Patient Information Leaﬂets (PILs) – the instructions that accompany medications in Europe – problematises the reception of these texts. There is at the same time growing understanding of the mediating role of trust in risk communication. This paper aims to analyse how risk is discursively constructed in PILs, and to identify and analyse discourses that are associated with trust-generation. The corpus (nine PILs chosen from the British online PIL bank, www.medicines.org.uk) is analysed using Foucauldian (1972) discourse analysis: speciﬁcally, this involves identifying the functions of the statements that constitute the discourses. A discourse analysis of the corpus of PILs reveals that the discourse of risk revolves around statements of the potential harm that may be caused by taking the medication, whilst trust is constructed through three discourses: the discourses that relate to competence and care, in accordance with the trust theories of Poortinga/Pidgeon (2003) and Earle (2010), and a third discourse, corporate accountability, which functions to construct an ethical (trustworthy) identity for the company. This paper contributes to PIL literature in the following ways: it introduces a methodology that has not been used before in relation to these texts, namely, Foucauldian discourse analysis; it helps to identify the presence of trust-generating discourses in PILs; and analysing the discourses of risk and trust at statement-level facilitates a better understanding of how these discourses function in texts that are generally not well-received by the patients for whom they are intended.